Australia: Identity, Fear and Governance in the 21st Century - Pietsch, Juliet (ANU Press, 2012)
The latter years of the first decade of the twenty-first century were characterised by an enormous amount of challenge and change to Australia and Australians. Australia's part in these challenges and changes is borne of our domestic and global ties, our orientation towards ourselves and others, and an ever increasing awareness of the interdependency of our world. Challenges and changes such as terrorism, climate change, human rights, community breakdown, work and livelihood, and crime are not new but they take on new variations and impact on us in different ways in times such as these. In this volume we consider these recent challenges and changes and how Australians themselves feel about them under three themes: identity, fear and governance. These themes suitably capture the concerns of Australians in times of such change. Identity is our sense of ourselves and how others see us. How is this affected by the increased presence of religious diversity, especially Islamic communities, and increased awareness of moral and political obligations towards Indigenous Australians? How is it affected by our curious but changing relationship with Asia? Fear is an emotional reaction to particular changes and challenges and produces particular responses from individuals, politicians, communities and nations alike; fear of crime, fear of terrorism and fear of change are all considered in this volume.